The game of life - Howe, Norma (New York : Crown, 1991)
With a name like Cairo, she's destined to be a little different. But what excuse do the other people in her family have for being so... well, weird? Her mom's a bingo frantic. Her dad's into collecting PKGs (that's patented kitchen gadgets). Her aunt Lucille has a serious eating problem. Her older sister Heather, an astrology freak, is threatening to marry a violent environmentalist. These people need her help! Sixteen-year-old Cairo feels as though she's the only one (besides her dog) with any sense at all -- until she meets a soulmate in the handsome and worldly-wise Rocky Nevin. They talk passionately about Vietnam, rootbeer, tennis, and the purpose of existence. Rocky's taking his time, but Cairo's certain he's worth the wait. Because as crazy as life is, things seem to have an even crazier way of working out...
Keywords: Family life -- Fiction